A framework for sustainable slum development based on zero waste concept: "Learn to Earn Model" - Elgizawy, Sally Maher (AUC Knowledge Fountain, 2019)
The rapid urbanization of the last century caused more slum formation resulting in numerous adverse effects and is considered a major problem facing developing countries specially Egypt. This research touches on the complexities of sustainable slum development specially dealing with slum dwellers in a trial to enhance their capacities and potential which would benefit the community and lead to the development of the slum. Teaching them new skills through the "Learn to Earn Model'', will help them generate income which turns the slum into a catalyst for the economy rather than a burden on it. Another major problem in developing countries nowadays is waste accumulation. Zero waste strategy dictates that waste moves from a linear system to being more cyclical according to cradle to cradle approach so that materials are used efficiently. Construction and demolition waste (C&D), representing a huge part of the solid waste stream, is the focus of this research. It is certain that C&D waste with its continuously increasing quantity has tremendous adverse effects on sustainability affecting the environment, the local community and the economy of the country itself. To tackle the problem of C&D waste in Egypt effectively a series of steps were undertaken; a thorough literature review on C&D waste in Egypt was conducted identifying a typical C&D waste stream and categorizing the components into likely to be recycled and others which are hard to recycle. Moreover, a quantification approach suitable for Egyptian projects was formulated and tested on 4 projects in Egypt and their construction waste index evaluated. The study on C&D waste revealed that gypsum and gypsum board waste is one of the main components in modern construction yet one of the less likely components to be recycled. This is mainly because of its suboptimal properties due to its mixing with other waste and the paper backing involved with the gypsum board waste. Extensive experimental work on recycling gypsum and gypsum board waste intends to produce an alternative brick able to mitigate the disadvantages of traditional brick by using waste as raw material and replacing the firing process often associated with bricks. The experimental work is divided in batches of experiments, with every batch, a new knowledge about recycling gypsum waste is gained. The first batch is intended to study the performance of similar commercial bricks to act as control as well as reach the optimum water to solid ratio for the gypsum waste to ensure good workability. Second batch was important to assess the effect of chemicals on the behavior of gypsum waste mix and it concluded that 0.9% Zinc Sulphate was proven to increase the compressive strength of the mix to required standards. Batch 3 investigated the effect of adding fibers like rice straw and mineral wool, however they showed no effect on compressive strength and increased the % absorption further. Batch 4 investigated the use of hydrophobic compounds to decrease the % absorption, commercial ones like water repellents, water-based paints and cold applied bitumen were used as well as natural ones like Agmin which proved to have a significant effect on absorption. It was experimentally proven that the optimum mix design for the gypsum waste brick is made of gypsum waste +0.9% zinc sulphate+35% cold bitumen. This mix satisfies all the required standards, Egyptian Standards and ASTM, and has similar or even better properties than the commercial bricks, however, bitumen is quite expensive and is considered a non-renewable polluting material. For that reason, batch 5 of experiments focused on using different grades of bitumen to minimize the cost and were proven to have the same effect on the gypsum waste brick. Moreover, to limit the use of bitumen, a trial using Agmin and cement bypass dust as replacement to part of the bitumen used, showed that up to 65% replacement of bitumen is possible without affecting the mechanical properties. The gypsum waste mix is intended to be used in producing an alternative brick made from gypsum waste and other decorative gypsum products like plaster ceiling rose and balusters hence saving energy, raw materials and conserving natural resources. The process of bricks production is intended to follow the old adobe technique for bricks manufacturing, which is low cost, not labor intensive and does not consume energy. A case study of an actual slum area called Ezbet el Nasr near Basateen area, Cairo, was undertaken to apply the Learn to Earn Model where the focus of slum development is on the slum dwellers themselves, teaching them new skill which helps them produce a marketable product and sell it as a source of income. One of the main activities of the LEM introduced in Ezbet el Nasr is gypsum and gypsum board waste recycling to produce gypsum waste bricks and other decorative items which can be sold for money or used in renovating already existing housing in the slum area. Actual implementation of LEM on Ezbet el Nasr showed that it is a complex process requiring institutional support to further promote the process of gypsum waste bricks production which would solve many of Egypt’s current problems